2016
DOI: 10.1038/nphys3671
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Hall effects in topological insulator heterostructures

Abstract: Geometry, both in momentum and in real space, plays an important role in the electronic dynamics of condensed matter systems. Among them, the Berry phase associated with nontrivial geometry can be an origin of the transverse motion of electrons, giving rise to various geometric e ects such as the anomalous 1 , spin 2 and topological Hall e ects 3-6 . Here, we report two unconventional manifestations of Hall physics: a sign-reversal of the anomalous Hall e ect, and the emergence of a topological Hall e ect in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
207
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(231 citation statements)
references
References 31 publications
19
207
3
2
Order By: Relevance
“…Recent theoretical studies predict that magnetic skyrmions on TI surface can be charged as well 29,30 . Transport measurements in magnetic TI heterostructures discovered the coexistence of the THE related to the real-space Berry curvature from skyrmions and the AHE related to momentum-space counterpart from SOC 31 , while the transport is dominated by the bulk states, leaving the surface transport ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical studies predict that magnetic skyrmions on TI surface can be charged as well 29,30 . Transport measurements in magnetic TI heterostructures discovered the coexistence of the THE related to the real-space Berry curvature from skyrmions and the AHE related to momentum-space counterpart from SOC 31 , while the transport is dominated by the bulk states, leaving the surface transport ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this emergent magnetic field does not necessarily need to be in momentum space, but can also exist in real space [10,11]. It is well known that when electrons flow in a nontrivial magnetic texture, they experience an emergent electromagnetic field [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that magnetically doped TI layers can be epitaxially grown on an undoped TI layer and vice versa to form the required FM-TI-FM sandwich heterostructures [23,26,27]. (Figs.…”
mentioning
confidence: 99%